1944
DOI: 10.1021/ie50418a012
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin Retention in Processed Meat

Abstract: The effects of time and temperature of processing on the retention of thiamine, riboflavin, niacin, and pantothenic acid in pork luncheon meat are discussed. The rate of thiamine destruction is doubled with an 18°F. increase in temperature as contrasted with a tenfold increase in the rate of destruction of heat-resistant bacteria. Under conditions which permit uniformly rapid heating of the INDUSTRIAL AND ENGINEERING CHEMISTRY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Release of bounded vitamins and, thus, a significant increase in the amount of B 1 +B 2 vitamins was observed in the experiments carried out at higher air velocities (3 and 5 m/s), while a decrease in the amount of these vitamins was observed at lower air velocities (1 and 2 m/s). In this sense, Greenwood et al (1944) observed that, at constant temperature, the degree of degradation of vitamin B 1 is a function of time, so the decrease in the amount of vitamins B 1 +B 2 is mainly controlled by the time of exposition to heat. Although the human body is somewhat efficient to absorb vitamins B 1 and B 2 , the absorption of vitamin B 2 requires the hydrolysis of the flavin coenzyme in the upper small intestine to free riboflavin, which is then absorbed (Merrill et al 1981).…”
Section: Vitamins Content In the Dried Applementioning
confidence: 99%
“…Release of bounded vitamins and, thus, a significant increase in the amount of B 1 +B 2 vitamins was observed in the experiments carried out at higher air velocities (3 and 5 m/s), while a decrease in the amount of these vitamins was observed at lower air velocities (1 and 2 m/s). In this sense, Greenwood et al (1944) observed that, at constant temperature, the degree of degradation of vitamin B 1 is a function of time, so the decrease in the amount of vitamins B 1 +B 2 is mainly controlled by the time of exposition to heat. Although the human body is somewhat efficient to absorb vitamins B 1 and B 2 , the absorption of vitamin B 2 requires the hydrolysis of the flavin coenzyme in the upper small intestine to free riboflavin, which is then absorbed (Merrill et al 1981).…”
Section: Vitamins Content In the Dried Applementioning
confidence: 99%
“…Effects of extrusion processing [ 119 , 120 ], gamma irradiation as a conservation technique [ 68 , 121 , 122 , 123 , 124 ], canning [ 125 , 126 , 127 ], freezing [ 89 , 126 ], storage conditions [ 81 , 86 , 105 , 126 , 128 , 129 , 130 , 131 ], and edible seed germination [ 90 , 94 , 95 , 96 , 132 , 133 ] on thiamine content in foods have also been reported.…”
Section: Thiamine—vitamin Bmentioning
confidence: 99%
“…Boiling, poaching, and frying of eggs lower riboflavin content by 6%, 18%, and 8%, respectively [ 107 ]. The canning process may result in a small decrease of riboflavin content in vegetables and mushrooms, as well as pork luncheon meat [ 125 , 126 ].…”
Section: Riboflavin—vitamin Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Greenwood et al [24] have first published a technique, which they used to study the destruction of thiamin in cured pork luncheon meat compared with microbial destruction. Greenwood et al [24] have first published a technique, which they used to study the destruction of thiamin in cured pork luncheon meat compared with microbial destruction.…”
Section: Acrylamide In Heated Foodsmentioning
confidence: 99%